2015
DOI: 10.1093/ejo/cjv071
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of periostin in the process of orthodontic tooth movement

Abstract: These authors contributed equally to this paper. SummaryAim: The process of orthodontic tooth movement (OTM) involves multiple mechanisms of action including bone and extracellular matrix remodelling, although the role of periodontal ligament (PDL) in this process is largely unknown. Periostin, which is highly expressed in the PDL, is known to be responsible for mechanical stimulation in maintaining the integrity of periodontal tissues. We hypothesize that this protein plays an important role during OTM. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…In this study, the change patterns of sclerostin expression in the compression and tension sites during tooth movement were different. Our result was partially in agreement with a study by Rangiani’ [36], who reported an increase in SOST expression at the compression site and a reduction in expression at the tension site 8 days after orthodontic force loading in a tooth movement model in mice. The different expression pattern of sclerostin in compression and tension sites during tooth movement was a novel finding, which indicated that additional research on the biological function of sclerostin in toothmovement is needed.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the change patterns of sclerostin expression in the compression and tension sites during tooth movement were different. Our result was partially in agreement with a study by Rangiani’ [36], who reported an increase in SOST expression at the compression site and a reduction in expression at the tension site 8 days after orthodontic force loading in a tooth movement model in mice. The different expression pattern of sclerostin in compression and tension sites during tooth movement was a novel finding, which indicated that additional research on the biological function of sclerostin in toothmovement is needed.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, explaining sclerostin expression and the role of sclerostin in tooth movement bone remodeling was necessary. Two recently published papers investigated sclerostin expression in tooth movement models [35, 36]; however, the researchers only studied the expression of sclerostin at a single time point. To our knowledge, this study is the first one to trace the expression pattern of sclerostin throughout an entire orthodontic cycle (four weeks) in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin has been shown to contribute to bone and periodontal tissue remodeling following mechanical stress in experimental models of tooth movement, and is closely related to mechanical sensing (Wilde et al, 2003;Kudo, 2011;Rangiani et al, 2016). The presence of periostin not only affects the composition of ECM, but also alters the physical properties of the ECM such as matrix stiffness that influence stem cell behavior (Guilak et al, 2009;Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are two areas that Postn has been examined in 1) periodontal surgery (Padial-Molina, et al, 2015) and 2) experimental tooth movement (Rangiani, et al, 2015, Wilde, et al, 2003). Using an observational prospective case-control study Padial-Molina and colleagues assessed Postn expression in patients with and without periodontitis.…”
Section: Periodontiummentioning
confidence: 99%
“…During experimental tooth movement, Postn expression has been shown to be upregulated in the compression sites compared to tension sites of the PDL following experimental tooth movement in mice (Wilde, et al, 2003). In a subsequent study by Rangiani and colleagues, they assessed experimental tooth movement, comparing the process directly in Postn −/− and Postn +/+ mice (Rangiani, et al, 2015). Interestingly, the process of tooth movement was significantly slower in Postn −/− mice compared to wild types, and this was concomitant with no change in sclerostin expression, but reduced numbers of osteoclasts and the integrity of collagen fibers was also significantly compromised.…”
Section: Periodontiummentioning
confidence: 99%